The impact of rural-urban migration on a village music culture: some implications for applied ethnomusicology - Avorgbedor, Daniel K. (African Music : Journal of the International Library of African Music, 1992)
Rural-urban migration, which is becoming a unique phenomenon in developing countries, constitutes a special challenge in ethnomusicology. Consequently materials, methods, and theory building in ethnomusicology are now being forced to "face the music" in urban areas. It is therefore my purpose to provide a detailed aspect of how rural-urban migration affects musical practice in a particular village in Ghana; and, second, to address specific problems derived from the village situation; and, finally, to explore how a more favourable situation could be created through the implementation of a suggested program of action from the perspective of applied ethnomusicology.